Before-after analysis of genetic and epigenetic markers in garlic: A 13-year experiment - Gimenez, Magali Diana; Garcia Lampasona, Sandra Claudia (2018)
Allium sativum is an important crop species in Argentina, one of the major garlic exporting countries in the world. Because garlic is an agamic propagated species, its breeding is based on the occurrence of plants with desirable traits, which are attributed to genetic mutations. In this work, we took advantage of a long term field experiment in a garlic line destined to genetic improvement to evaluate bulb weight and genetic and epigenetic stability and dynamics over 13 years. Average bulb weight increased from 65.3 g in the first year to 84.8 g the 13th year. Using AFLP (Amplified Fragment Length Polymorphism) and MSAP (Methylation Sensitive Amplified Polymorphism) techniques, we assessed genetic and epigenetic stability in plants of A. sativum taken at first, third and 13th year of field culture. We detected that 82.47 and 19.61% of the AFLP and MSAP fragments were present in the tree years of sampling. The application of selection pressure led to a reduction in genetic polymorphism and an increase of bulb weight, but did not influence epigenetic polymorphism, indicating that it is independent of genetic variability. We detected changes in the amount of each methylation pattern (unmethylated, hemimethylated and internally methylated) among the different years analyzed while 82.47 and 19.61% of the genetic and epigenetical loci were stable during the time of culture. Although some epiloci showed stability along the 13 years of culture, others presented gradual variation, while others were polymorphic within samples from the same year of culture. Finally, we discussed the implications of the high epigenetic variability of an agamic propagated species and its possible effect on the phenotype.